The formation of the young massive cluster B1 in the Antennae Galaxies (NGC 4038/NGC 4039) triggered by cloud–cloud collision. (3rd March 2021) - Tsuge, Kisetsu; Tachihara, Kengo; Fukui, Yasuo; Sano, Hidetoshi; Tokuda, Kazuki; Ueda, Junko; Iono, Daisuke
Abstract: The Antennae Galaxies, one of major mergers, are a starburst. Tsuge et al. (2020, PASJ, 73, S35) showed that the five giant molecular complexes in the Antennae Galaxies have signatures of cloud–cloud collisions based on the Atacama Large Millimeter Array (ALMA) archival data with 60 pc resolution. In the present work we analyzed the new CO data toward the super star cluster (SSC) B1 with 14 pc resolution obtained with ALMA, and confirm that two clouds show a complementary distribution with a displacement of ∼70 pc as well as connecting bridge features between them. The complementary distribution shows a good correspondence with the theoretical collision model (Takahira et al. 2014, ApJ, 792, 63), and the distribution indicates that the formation of SSC B1 with ∼10 6 M ⊙ was consistent with the trigger of cloud–cloud collision on a time scale of ∼1 Myr, which is consistent with the cluster age. It is likely that SSC B1 was formed from molecular gas of ∼10 7 M ⊙ with a star formation efficiency of $\sim\! 10%$ in 1 Myr. We identify a few places where additional clusters are forming. Detailed gas motion indicates that the stellar feedback in the accelerating gas is not effective, while the ionization plays a role in evacuating the gas around the clusters at a ∼20 pc radius. The results have revealed the details of the parent gas where a cluster having a mass similar to a globular is being formed.